ANALISIS PENILAIAN KINERJA PT PELABUHAN INDONESIA IV (PERSERO) CABANG MAKASSAR DENGAN PENDEKATAN BALANCED SCORECARD - Suci Hijrah Dini (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2019)
This Research aims to : (1) analyze the effect of financial perspective for the performance of PT. Pelabuhan Indonesia IV (Persero) Cabang Makassar. (2) analyze the effect of customer perspective for the performance of PT. Pelabuhan Indonesia IV (Persero) Cabang Makassar. (3) analyze the effect of internal business perspective for the performance of PT. Pelabuhan Indonesia IV (Persero) Cabang Makassar.(4) analyze the effect of learning and growth perspective for the performance of PT. Pelabuhan Indonesia IV (Persero) Cabang Makassar. The data used are primary data. All data in this study collected by using questioner. Questioner given away to98 employees in PT. Pelabuhan Indonesia IV (Persero) Cabang Makassar.Data were analyzed using path analysis using SPSS for windows version 23.00. The result of research indicate that variable of : financial perspective, customer perspective, internal businees perspective and learning and growth perspective a simultaneustly and partially have positif and signifikanforthe performance of PT. Pelabuhan Indonesia IV (Persero) Cabang Makassar.